LITERATURE REVIEW ENTERPRISE INFORMATION SYSTEM USER SATISFACTION: DATA QUALITY ANALYSIS, INFORMATION QUALITY, AND SERVICE QUALITY - Beatrix, Grace (Dinasti Publisher, 2022)
Previous research is very important in scientific research or article. The relevant riset serves to strengthen the theory and the nagging of relationships or influences between variables. This article reviews factors that affect human resource enterprise information system user satisfaction, namely: Quality of Service, Quality of Information, and Quality of Systems, a literature study of Human Resource Management. The purpose of writing this article is to build a hypothesis of influence between variables for use in future research. The results of this literature review article are 1) Service Quality affects Human Resource Enterprise Information System User Satisfaction; 2) Information Quality affects Human Resource Enterprise Information System User Satisfaction, and 3) System Quality affects Human Resource Enterprise Information System User Satisfaction.